The Building of Consent: Initiation Rituals and Students' Power Relations in the University of Coimbra - Estanque, Elísio (2017)
This article covers three areas. The first (i) gives a brief historical overview of the University of Coimbra and outlines some of the academic traditions, as well as violent behaviour associated with the initiation rituals (known as Praxe). The second area (ii) explores the possible links between these rituals and various cultural and socio-political movements, especially during the authoritarian regime. Finally (iii), the study analyses the most recent trends of the phenomenon in Portugal. The research purpose is to reveal the massive dimension of this phenomenon and its specificities in the case of Coimbra, the hometown of the Portuguese university where all these rituals started, about 700 years ago. The article is based upon a qualitative and reflexive methodology, and the empirical data has been gathered, firstly, from historical documentation and secondly, by permanent and direct observation over more than 30 years of living and dealing (as a professor) with the daily life of students in this city. This became a public issue after a number of controversial incidents, with trends very often shifting towards abuse, humiliation and violence. The culture of submission in the face of power that most initiation rituals foster seems to express a dormant tendency in society, where consumerist individualism is combined in a perverse way with mechanisms of avoidance and unconditional surrender to disciplinary rationales of a despotic nature.